Materials and the environment : eco-informed material choice - Ashby, M. F. (Amsterdam ; Boston : Butterworth-Heinemann/Elsevier, 2009)
"As concerns for the environment grows, there is a corresponding trend to incorporate sustainability into engineering education. Materials and the Environment addresses this growing concern with this full-length text devoted exclusively to the environmental aspects of materials."--BOOK JACKET.
Introduction : material dependence -- Resource consumption and its drivers -- The materials life cycle -- End of first life : a problem or a resource? -- The long reach of legislation -- Ecodata : values, sources, precision -- Eco-audits and eco-audit tools -- Selection strategies -- Eco-informed material selection -- Sustainability : living on renewables -- The bigger picture : future options -- Material profiles -- Appendix : useful numbers and conversions.
Includes bibliographical references and index.
Keywords: Materials -- Environmental aspects